Analysis of Marriage Postponement Among STDI Imam Syafi’i Jember Students: Analisis Fenomena Penundaan Pernikahan Mahasiswa STDI Imam Syafi’i Jember - Nur Adli Zal Farizi; Musthofa; Muhammad Salman Fikri Ramadhan; Gati Rianto; Muhammad Amrullah (PT Syamilah Literasi Islami, 2024)
The phenomenon of postponing marriage is when individuals or couples choose to postpone their marriage from an age that is considered a common time for marriage. Dirasat Islamiyah Imam Syafi'i Jember High School is a tertiary institution located in Sumbersari District, Jember Regency, East Java Province. The purpose of this research is to determine the phenomenon of postponing marriage for Imam Syafi'i Jember High School Dirasat Islamiyah (STDI) students, the impact of postponing marriage, as well as the opinions of mazhab ulama regarding postponing marriage. This research uses a qualitative approach with a case study type of research. The results of this research show that: (1) The phenomenon of postponing marriage for STDI Imam Syafi'i Jember students who have reached the common age for marriage is caused by several factors, namely: a) economic factors, b) educational factors, c) cultural factors and values. family values, and d) mental readiness factors. (2) The impact of postponing marriage on STDI Imam Syafi'i Jember students, namely: a) positive impacts, including: it is easier to focus on studying, has more free time, has less freedom and expenses. b) negative impacts, including: difficulty controlling desires, loneliness and confusion, and difficulty managing finances. (3) The opinion of mazhab scholars regarding the law of postponing marriage is divided into two: a) it is makruh and even haram if there is no excuse, and b) it is permissible if there is a syar'i excuse.